Cavernous hemangioma originating from the cervical vagus nerve masquerading as a schwannoma: a case report - Lu, Yiyang; Zhu, Guochen; Hu, Jianxin; Lv, Hui; Xiao, Yan (Frontiers in Surgery, 2026)
Peripheral nerve cavernous hemangioma refers to cavernous vascular malformations occurring on peripheral nerves outside the cranial and spinal nerves. It is a rare non-neoplastic condition. We report a case of a 53-year-old female patient who presented with a painless mass in the right mid-lower neck and a foreign body sensation in the pharynx for five months. Preoperative ultrasonography (US), computed tomography (CT), and magnetic resonance imaging (MRI) revealed a well-delineated lesion with minimal blood flow signals, heterogeneous enhancement on contrast-enhanced CT and T1-weighted imaging, and high signal intensity on T2-weighted imaging. The patient underwent complete surgical excision of the lesion. Intraoperatively, the lesion was found to be located between the epineurium and perineurium of the vagus nerve and was completely enucleated. Postoperative histopathological and immunohistochemical analyses confirmed the diagnosis of cavernous hemangioma. The patient recovered without complications and exhibited no hoarseness or other neurological deficits postoperatively. No signs of lesion recurrence were observed during a 28-month follow-up. This case suggests that when managing tumors of the cervical vagus nerve, vascular lesions should be included in the differential diagnosis, although such instances are relatively rare.